Bacterial Diversity in Native Heart Valves in Infective Endocarditis - Anna Sinitskaya; Alexander Kostyunin; Maxim Asanov; Maria Khutornaya; Anastasia Klyueva; Alyona Poddubnyak; Alexey Tupikin; Marsel Kabilov; Maxim Sinitsky (Biomedicines)
Background: Infective endocarditis (IE) is an infectious disease caused by the hematogenous dissemination of bacteria into heart valves. Improving the identification of pathogens that cause IE is important to increase the effectiveness of its therapy and reduce the mortality caused by this pathology. Methods: Ten native heart valves obtained from IE patients undergoing heart valve replacements were analyzed. Bacterial invasion in the heart valves was studied by Gram staining of histological sections. Histopathological changes accompanied with bacterial invasion were studied by immunohistochemical analysis of pan-leukocyte marker CD45, platelet marker CD41, and neutrophil myeloperoxidase. The taxonomic diversity of the bacteria was analyzed using 16S rRNA metabarcoding. Results: Gram staining of the histological sections revealed bacterial cells localized on the atrial surface at the leaflet’s free edge or on the ventricular surface at the leaflet’s base within fibrin deposits in only three of the studied heart valves. Bacterial colonies were co-localized with microthrombi (CD41+ cells) containing single leucocytes (CD45+ cells), represented by segmented neutrophils. As a result of 16S rRNA metabarcoding, we detected the following bacterial genera: Pseudomonas (70% of the studied heart valves), Roseateles (60%), Acinetobacter (40%), Sphingomonas (40%), Enterococcus (30%), Reyranella (20%), Sphingobium (20%), Streptococcus (20%), Agrobacterium (20%), Ralstonia (10%), and Bacillus (10%). Conclusions: A number of opportunistic microorganisms that could not be detected by routine laboratory tests and were not eliminated during antibiotic therapy were identified in the IE-affected heart valves. The obtained results show the importance of 16S rRNA metabarcoding of heart valves removed due to IE not only as an independent diagnostic method but also as a highly accurate approach that complements routine tests for pathogen identification.